PIXELS, PODCASTS, AND PEDAGOGY: DEVELOPING MULTIMODAL LISTENING AND SPEAKING MATERIALS FOR EFL PRE-SERVICE TEACHERS - I Dewa Gede Rat Dwiyana Putra; I Gusti Ngurah Agung Wijaya Mahardika; I Putu Andre Suhardiana (Wiralodra English Journal, 2026)
This study concentrated on examining the attributes, subjects, and activity choices for multimodal listening and speaking materials for EFL pre-service teachers. This research and development study used a four-step process: design, develop, review, and revise, based on the Dick and Carey System Approach Model. This study found that when designing multimodal listening and speaking materials, it is needed to think about how they fit with the goals of the study, how to encourage active learning and participation, how to make them flexible and adaptable, how to use technology, how to be culturally competent and inclusive, how to make the language clear, how to arrange and design the materials, and how to get feedback and make improvements. The procedure of developing the material includes gathering the parts, creating the content, getting expert opinions, and editing the content. The focus was on grammar problems, photo selection, formatting, and storing the material. The research shows that multimodal materials function as ecosystems that integrate theory, practice, and cultural responsiveness to facilitate the growth of pre-service teachers. Longitudinal studies should be conducted in future research to see how the materials affect how well students learn and how engaged they are in different classroom settings.